Postpartum Cervical Cancer Screening Adequacy and Results: Comparison of Results 2-3 Versus 6-8 Weeks Postpartum [20E]. (May 2017) - Carty, Jenava; Batig, Alison
Abstract : INTRODUCTION: Postpartum follow up earlier than the traditional 6-8 week interval has been proposed as a means to enhance care provision to women after childbirth. Our study's objective was to compare cervical cancer screening adequacy and results when screening was performed either 2-3 or 6-8 weeks postpartum. METHODS: The data for this study was obtained as part of a randomized controlled trial that recruited primiparous women who delivered at term with an expressed intent to breastfeed to postpartum appointment intervals of either 2-3 or 6-8 weeks following childbirth. When cervical cancer screening was performed, the results were reviewed for adequacy and findings. The results were compared for each group using chi-squared analysis; adequacy was compared using an odds ratio with 95% confidence interval. RESULTS: The rates of cytologic adequacy were comparable between the group (95.0 versus 100% in the 6-8 week group, p=0.21); the odds ratio for "unsatisfactory" cytology in the 2-3 week follow up group was 0.06 (95% CI < 0.01-41.8). The distribution of cytologic results was comparable between the group (p=0.09); no one in either group had a high-grade cytologic result or cervical cancer. When performed, the rates of positive and negative high-risk human papillomavirus results was comparable between the groups (p=0.92). CONCLUSION: Our study indicates that cervical cancer screening can be completed earlier during the postpartum period than traditionally accepted without compromising cytologic adequacy or results. This information may be useful in shaping future recommendations regarding the timing and medical services provided during the postpartum period.